2016
DOI: 10.1386/jaah.7.3.347_1
|View full text |Cite
|
Sign up to set email alerts
|

‘I’m not a therapist you know... I’m an artist’: Facilitating well-being and basic psychological needs satisfaction through community arts participation

Abstract: The role of the artist is crucial to the success of arts for health initiatives yet remains underexplored in the research literature. This article examines the practice of arts facilitation through the lens of self-determination theory (SDT). Fourteen interviews with artists leading projects for older adults across three settings were subject to a secondary thematic analysis. A hybrid approach was adopted with themes developed inductively and deductively. Artists were found to satisfy participants' basic psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…In recognising the diversity of terminology identified in the literature (Swindells et al . ), a significant challenge was to determine which vocabulary to adopt in the curriculum. The Course Team were eager to maintain the broad range of potential career trajectories for which the course has become known, but also to deliver suitably rich, in‐depth teaching on each area for undergraduate study (QAA ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In recognising the diversity of terminology identified in the literature (Swindells et al . ), a significant challenge was to determine which vocabulary to adopt in the curriculum. The Course Team were eager to maintain the broad range of potential career trajectories for which the course has become known, but also to deliver suitably rich, in‐depth teaching on each area for undergraduate study (QAA ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while the course title might not directly represent some of the specific sub‐disciplines of the practice, and the inclusion and connotation of the word ‘therapeutic’ can be problematic (Swindells et al . ), students reported that the broadness of the title and its lack of focus on one specific profession enabled introduction to a wide range of disciplines which students might not otherwise have sought out or pursued. While a shift in course title may attract a different demographic and perhaps enable a tighter alignment between applicants and a specific trajectory such as Arts in Health, the Course Team are eager to maintain an inclusive stance which celebrates students’ diverse ambitions and enables pursuit of a portfolio career in considering the vast array of professional opportunities the course and discipline affords.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations